High-performance Al2O3-SiC-C castable using flowing carbon source and preparation method thereof

By using pretreated flow tar as carbon source in the Al2O3-SiC-C castable, the problem of uneven dispersion of spherical asphalt is solved, and the mechanical properties of the material are significantly improved, and the resistance to oxidation and slag corrosion resistance of the material is significantly improved.

CN119661202APending Publication Date: 2025-03-21YIXING REFRACTORY EQUIP & MATERIAL FACTORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411862410.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the existing Al2O3-SiC-C castable, the dispersion of spherical asphalt is uneven, resulting in a decrease in material stability and affecting service life.

Method used

Tar with fluidity at room temperature is used as the carbon source, and its viscosity is reduced through pretreatment, which promotes its dispersion in the castable and increases constructionability.

Benefits of technology

The mechanical properties, high-temperature properties, oxidation and slag corrosion resistance of Al2O3-SiC-C castable are improved, the flexural strength and compressive strength of the room temperature are increased by 30% or more, and the oxidation/slag corrosion index is reduced by more than 45%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-performance Al2O3-SiC-C castable using a flowing carbon source and a preparation method of the high-performance Al2O3-SiC-C castable, and belongs to the technical field of refractory materials. The refractory material is prepared from the following components in parts by weight: 45-60 parts of brown aluminum oxide, 10-20 parts of silicon carbide, 5-10 parts of compact corundum, 10-15 parts of a mixture of activated aluminum oxide micro powder and silicon micro powder, 3-6 parts of calcium aluminate cement, 2-6 parts of tar, 0.15-0.3 part of a dispersing agent, 0.1-0.3 part of metal aluminum powder, 0.3-0.5 part of metal silicon powder and 0.1-0.6 part of a silane coupling agent or ethyl silicate. The problem that the dispersity of the carbon source in the Al2O3-SiC-C castable is poor is effectively solved, and the mechanical property, the high-temperature property, the oxidation resistance and the slag corrosion resistance are improved; and the breaking strength and the compression strength of a sample subjected to heat treatment at 1200 DEG C for 3 hours are respectively improved by 30% and 15% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a high-performance Al2O3-SiC-C castable using a mobile carbon source and a preparation method thereof. Background Art

[0002] The carbon material in Al2O3-SiC-C castable can improve the thermal shock stability of the material, prevent the slag from penetrating into the material, improve the corrosion resistance of the material, and thus extend the service life of the castable. When studying Al2O3-SiC-C castable, the selection of carbon raw materials needs to consider multiple factors to achieve the best ratio and effect.

[0003] A common carbon source choice in industry is spherical pitch. Due to its spherical shape, it can increase its dispersibility within the castable matrix and better perform its performance. However, the residual carbon rate of spherical pitch is low, and its spherical structure easily leaves holes in situ in the sample after burning, which accelerates the oxidation of the castable, resulting in a decrease in the stability of the material and affecting the service life of the castable. Spherical pitch has colloidal properties during the heating process, and relies on softening during the heating process to penetrate, volatilize and condense into the pores inside the castable, thereby increasing the density of the material and thus improving the overall performance of the castable.

[0004] Based on the mechanism of action of spherical asphalt in castables, introducing a carbon source with fluidity at room temperature into the castable is beneficial to improving the dispersion of carbon in the castable matrix and enhancing the overall performance of the castable. Tar, as the precursor of asphalt, is a viscous liquid at room temperature and has fluidity. Therefore, tar can be used as a carbon source to solve the disadvantage of uneven dispersion of spherical asphalt in castables. If tar is directly added to the castable, its viscous liquid state will seriously affect the workability. Therefore, the introduction of tar into the castable requires pretreatment of the tar to reduce its viscosity at room temperature, promote its dispersion in the castable, and increase the workability of the castable. Summary of the invention

[0005] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a high-performance Al2O3-SiC-C castable using a mobile carbon source, which has high mechanical properties and anti-oxidation and anti-slag corrosion properties; another technical problem to be solved by the present invention is to provide a method for preparing a high-performance Al2O3-SiC-C castable using a mobile carbon source.

[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] A high performance Al2O3-SiC-C castable using a mobile carbon source is made of the following components in parts by weight:

[0008] 45~60 parts of brown corundum, 10~20 parts of silicon carbide, 5~10 parts of dense corundum, 10~15 parts of a mixture of activated alumina micropowder and silicon micropowder, 3~6 parts of calcium aluminate cement, 2~6 parts of tar, 0.15~0.3 parts of dispersant, 0.1~0.3 parts of metallic aluminum powder, 0.3~0.5 parts of metallic silicon powder, 0.1~0.6 parts of silane coupling agent or ethyl silicate.

[0009] Preferably, the high-performance Al2O3-SiC-C castable using a mobile carbon source is made of the following components in parts by weight: 50-55 parts of brown corundum, 17-18 parts of silicon carbide, 8-10 parts of dense corundum, 10-12 parts of a mixture of activated alumina micropowder and silicon micropowder, 3-5 parts of calcium aluminate cement, 3-5 parts of tar, 0.2-0.3 parts of a dispersant, 0.1 parts of metallic aluminum powder, 0.4 parts of metallic silicon powder, and 0.3-0.5 parts of a silane coupling agent or ethyl silicate.

[0010] Preferably, the high-performance Al2O3-SiC-C castable using a mobile carbon source is made of the following components in parts by weight: 55 parts of brown corundum, 17-18 parts of silicon carbide, 9 parts of dense corundum, 11 parts of a mixture of activated alumina micropowder and silicon micropowder, 4 parts of calcium aluminate cement, 3-4 parts of tar, 0.2 parts of dispersant, 0.1 parts of metallic aluminum powder, 0.4 parts of metallic silicon powder, and 0.3-0.4 parts of silane coupling agent or ethyl silicate.

[0011] Preferably, the high-performance Al2O3-SiC-C castable using a mobile carbon source is made of the following components in parts by weight: 55 parts of brown corundum, 17 parts of silicon carbide, 9 parts of dense corundum, 11 parts of a mixture of activated alumina micropowder and silicon micropowder, 4 parts of calcium aluminate cement, 4 parts of tar, 0.2 parts of dispersant, 0.1 parts of metallic aluminum powder, 0.4 parts of metallic silicon powder, and 0.4 parts of ethyl silicate.

[0012] Preferably, the dispersant is a mixture of FS20 and sodium hexametaphosphate.

[0013] Preferably, the mass ratio of FS20 to sodium hexametaphosphate is 1:1.

[0014] Preferably, in the mixture of activated alumina micropowder and silicon micropowder, the mass ratio of activated alumina micropowder to silicon micropowder is 7:3.

[0015] Preferably, the particle size of the brown corundum is ≤8 mm, and the particle size of the dense corundum powder is ≤0.0374 mm.

[0016] Preferably, in the mixture of activated alumina micropowder and silicon micropowder, the particle size of the activated alumina micropowder is ≤0.0374 mm, and the particle size of the silicon micropowder is ≤0.0374 mm.

[0017] A method for preparing the high-performance Al2O3-SiC-C castable using a mobile carbon source, the preparation process is: brown corundum, silicon carbide, dense corundum, a mixture of activated alumina micropowder and silicon micropowder, calcium aluminate cement, metal silicon powder, metal aluminum powder and a dispersant are mixed evenly by a mixer, and then tar suspension and water are added for stirring; after stirring evenly, the stirred raw materials are poured into a mold, and cast on a vibration table to obtain the Al2O3-SiC-C castable.

[0018] Preferably, the tar suspension is prepared by keeping the tar in an oven at 70°C for 30 minutes, adding a silane coupling agent or ethyl silicate and stirring, and after the stirring is completed, cooling to room temperature and adding water to obtain the tar suspension.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses tar with fluidity at room temperature as a carbon source to prepare an Al2O3-SiC-C castable, which effectively solves the problem of poor dispersion of the carbon source in the Al2O3-SiC-C castable, and improves the mechanical properties, high temperature properties, and oxidation resistance and slag corrosion resistance of the Al2O3-SiC-C castable; wherein the room-temperature flexural strength and room-temperature compressive strength of the sample after heat treatment at 1200°C for 3 hours are increased by 30% and 15% respectively; the room-temperature flexural strength and room-temperature compressive strength of the sample after heat treatment at 1500°C for 3 hours are increased by at least 10%; the oxidation / slag corrosion index after heat treatment at 1500°C for 3 hours is reduced by more than 45%;

[0021] (2) The tar viscosity reducer used in the present invention can effectively reduce the viscosity of tar, and the tar suspension exhibits shear thinning properties, which promotes its dispersion in the castable and increases the workability of the castable. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following embodiments, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.

[0023] The specifications of the brown corundum particles used in the following examples are: Al2O3 content is 96.12wt.%, and the particle size of the particles is ≤8mm;

[0024] The specifications of silicon carbide powder are as follows: the particle sizes of fine powder are 0~1mm and 0~0.074mm, and the mixing mass ratio of the two powder particle sizes is 1:1.

[0025] The specifications of dense corundum powder are: Al2O3 content is 98.87wt.%, SiO2 content is 0.23wt.%, and the particle size of fine powder is ≤0.0374mm;

[0026] The specifications of the mixture of activated alumina micropowder and silicon micropowder are as follows: the particle size of the fine powder is ≤0.0374mm, wherein the mixed mass ratio of activated alumina micropowder and silicon micropowder is 7:3. The content of Al2O3 in the active Al2O3 micropowder is 99.30wt.%; the content of SiO2 in the silicon micropowder is 97.26 wt.%.

[0027] The model of calcium aluminate cement is Secar 71, the content of Al2O3 is 70.5 wt.%, and the content of CaO is 29.1 wt.%.

[0028] Tar is a viscous liquid; tar, as the precursor of asphalt, is liquid at room temperature; spherical asphalt is spherical particles at room temperature with a particle size of 0~1mm.

[0029] The dispersant is a mixture of FS20 and sodium hexametaphosphate, wherein the mass ratio of FS20 to sodium hexametaphosphate is 1:1; FS20 is FS20 polymer water reducer produced by BASF of Germany.

[0030] The Si content in the metallic silicon powder is ≥98 wt.%.

[0031] The tar viscosity reducer is a silane coupling agent or ethyl silicate. The model of the silane coupling agent is Kh570, and the purity of ethyl silicate is ≥99.0%.

[0032] Example 1

[0033] A method for preparing a high-performance Al2O3-SiC-C castable using a mobile carbon source comprises the following steps:

[0034] 1) Place a beaker containing 3 parts of tar in a 70°C oven for 30 minutes, then add 0.3 parts of silane coupling agent and stir for 5 minutes, cool to room temperature, add 1 part of water to obtain a tar suspension;

[0035] 2) 55 parts of brown corundum, 18 parts of silicon carbide, 9 parts of dense corundum, 11 parts of a mixture of activated alumina micropowder and silicon micropowder, 4 parts of calcium aluminate cement, 0.4 parts of metallic silicon powder, 0.1 parts of metallic aluminum powder, and 0.2 parts of a dispersant were mixed in a mixer for 2 minutes; after mixing evenly, the tar suspension prepared in step 1) and 4 parts of water were added and stirred for 2 minutes. After stirring evenly, the stirred raw materials were poured into a mold and cast on a vibration table to obtain an Al2O3-SiC-C castable.

[0036] Example 2

[0037] A method for preparing a high-performance Al2O3-SiC-C castable using a mobile carbon source comprises the following steps:

[0038] 1) Place a beaker containing 4 parts of tar in a 70°C oven and keep warm for 30 minutes, then add 0.4 parts of ethyl silicate and stir for 5 minutes, cool to room temperature and add 1 part of water to obtain a tar suspension;

[0039] 2) 55 parts of brown corundum, 17 parts of silicon carbide, 9 parts of dense corundum, 11 parts of a mixture of activated alumina micropowder and silicon micropowder, 4 parts of calcium aluminate cement, 0.4 parts of metallic silicon powder, 0.1 parts of metallic aluminum powder, and 0.2 parts of a dispersant were mixed in a mixer for 2 minutes; after mixing evenly, the tar suspension prepared in step 1) and 4 parts of water were added and stirred for 2 minutes. After stirring evenly, the stirred raw materials were poured into a mold and cast on a vibration table to obtain an Al2O3-SiC-C castable.

[0040] Example 3

[0041] When preparing the Al2O3-SiC-C castable, 0.3 parts of ethyl silicate was added, and the remaining components and preparation method were the same as those in Example 1.

[0042] Example 4

[0043] When preparing the Al2O3-SiC-C castable, 0.4 parts of silane coupling agent was added, and the remaining components and preparation method were the same as those in Example 2.

[0044] Example 5

[0045] When preparing the Al2O3-SiC-C castable, 18 parts of silicon carbide were added, and the remaining components and preparation method were the same as those in Example 2.

[0046] Comparative Example 1

[0047] 55 parts of brown corundum, 18 parts of silicon carbide, 9 parts of dense corundum, 3 parts of spherical asphalt (particle size is 0-1 mm), 11 parts of a mixture of activated alumina micropowder and silicon micropowder, 4 parts of calcium aluminate cement, 0.4 parts of metallic silicon powder, 0.1 parts of metallic aluminum powder, and 0.2 parts of dispersant are mixed in a mixer for 2 minutes; after mixing evenly, 5 parts of water are added and stirred for 2 minutes. After stirring evenly, the stirred raw materials are poured into a mold and cast on a vibration table to obtain an Al2O3-SiC-C castable.

[0048] The Al2O3-SiC-C castables prepared in Examples 1 to 5 and Comparative Example 1 were subjected to performance tests, and the results are shown in Table 1. The oxidation corrosion index is the ratio of the area of ​​the region not enriched by carbon to the initial area of ​​the cross section of the castable sample. The larger the ratio, the more serious the oxidation; the slag corrosion index is the ratio of the slag corrosion area of ​​the crucible hole to the initial area of ​​the crucible hole of the cross section of the static slag resistance sample. The larger the ratio, the more serious the slag corrosion.

[0049] Table 1 Performance indexes of Al2O3-SiC-C castables prepared in Examples 1 to 5 and Comparative Example 1

[0050]

[0051] As can be seen from Table 1, the Al2O3-SiC-C castable prepared by the present invention using tar effectively solves the problem of poor dispersion of carbon source in the Al2O3-SiC-C castable, and increases the mechanical properties, high temperature properties, and oxidation resistance and slag erosion resistance of the Al2O3-SiC-C castable. Compared with Comparative Example 1, the room temperature flexural strength and room temperature compressive strength of the sample of the Al2O3-SiC-C castable prepared by the present invention after heat treatment at 1200℃ for 3h are increased by 30% and 15% respectively; the room temperature flexural strength and room temperature compressive strength of the sample after heat treatment at 1500℃ for 3h are increased by at least 10%; the oxidation / slag erosion index after heat treatment at 1500℃ for 3h is reduced by more than 45%.

[0052] The viscosity of the tar suspensions prepared in Examples 1 to 4 of the present invention and Comparative Example 1 and the untreated tar (original tar) was measured, and the results are shown in Table 2. The viscosity result of Example 5 is the same as that of Example 2. Among them, the viscosity of the untreated tar at a low shear rate exceeds the range of the viscometer.

[0053] Table 2 Viscosity results of tar suspensions prepared in Examples 1 to 4 and Comparative Example 1 and original tar

[0054]

[0055] As shown in Table 2, silane coupling agent and ethyl silicate are amphiphilic polymers with lipophilic and hydrophilic properties. Adding amphiphilic polymers to tar can make tar molecules disperse evenly. Based on this principle, the present invention uses a tar viscosity reducer to effectively reduce the viscosity of tar, and the tar suspension exhibits a shear-thinning property. The shear-thinning phenomenon is that the viscosity decreases with the increase of shear rate or shear stress. In fluid mechanics, shear-thinning fluids are suitable for casting and molding of castables, which promotes their dispersion in castables and increases the workability of castables.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high performance Al2O3-SiC-C castable using a mobile carbon source, characterized in that: Made from the following components in parts by weight: 45~60 parts of brown corundum, 10~20 parts of silicon carbide, 5~10 parts of dense corundum, 10~15 parts of a mixture of activated alumina micropowder and silicon micropowder, 3~6 parts of calcium aluminate cement, 2~6 parts of tar, 0.15~0.3 parts of dispersant, 0.1~0.3 parts of metallic aluminum powder, 0.3~0.5 parts of metallic silicon powder, 0.1~0.6 parts of silane coupling agent or ethyl silicate.

2. The high performance Al2O3-SiC-C castable using a mobile carbon source according to claim 1, characterized in that: Made from the following components in parts by weight: 50~55 parts of brown corundum, 17~18 parts of silicon carbide, 8~10 parts of dense corundum, 10~12 parts of a mixture of activated alumina micropowder and silicon micropowder, 3~5 parts of calcium aluminate cement, 3~5 parts of tar, 0.2~0.3 parts of dispersant, 0.1 parts of metallic aluminum powder, 0.4 parts of metallic silicon powder, 0.3~0.5 parts of silane coupling agent or ethyl silicate.

3. The high performance Al2O3-SiC-C castable using a mobile carbon source according to claim 2, characterized in that: Made from the following components in parts by weight: 55 parts of brown corundum, 17-18 parts of silicon carbide, 9 parts of dense corundum, 11 parts of a mixture of activated alumina micropowder and silicon micropowder, 4 parts of calcium aluminate cement, 3-4 parts of tar, 0.2 parts of dispersant, 0.1 parts of metallic aluminum powder, 0.4 parts of metallic silicon powder, 0.3-0.4 parts of silane coupling agent or ethyl silicate.

4. The high performance Al2O3-SiC-C castable using a mobile carbon source according to claim 3, characterized in that: Made from the following components in parts by weight: 55 parts of brown corundum, 17 parts of silicon carbide, 9 parts of dense corundum, 11 parts of a mixture of activated alumina micropowder and silicon micropowder, 4 parts of calcium aluminate cement, 4 parts of tar, 0.2 parts of dispersant, 0.1 parts of metallic aluminum powder, 0.4 parts of metallic silicon powder, and 0.4 parts of ethyl silicate.

5. The high performance Al2O3-SiC-C castable using a mobile carbon source according to claim 1, characterized in that: The dispersant is a mixture of FS20 and sodium hexametaphosphate.

6. The high performance Al2O3-SiC-C castable using a mobile carbon source according to claim 1, characterized in that: In the mixture of the activated alumina micropowder and the silicon micropowder, the mass ratio of the activated alumina micropowder to the silicon micropowder is 7:

3.

7. The high performance Al2O3-SiC-C castable using a mobile carbon source according to claim 1, characterized in that: The particle size of the brown corundum is ≤8mm, and the particle size of the dense corundum powder is ≤0.0374mm.

8. The high performance Al2O3-SiC-C castable using a mobile carbon source according to claim 1, characterized in that: In the mixture of the activated alumina micropowder and the silicon micropowder, the particle size of the activated alumina micropowder is ≤0.0374 mm, and the particle size of the silicon micropowder is ≤0.0374 mm.

9. A method for preparing a high performance Al2O3-SiC-C castable using a mobile carbon source as claimed in any one of claims 1 to 8, characterized in that: The preparation process is as follows: brown corundum, silicon carbide, dense corundum, a mixture of activated alumina micropowder and silicon micropowder, calcium aluminate cement, metal silicon powder, metal aluminum powder and a dispersant are mixed evenly in a mixer, and then tar suspension and water are added for stirring; after stirring evenly, the stirred raw materials are poured into a mold, and cast on a vibration table to obtain an Al2O3-SiC-C castable.

10. The method for preparing a high performance Al2O3-SiC-C castable using a mobile carbon source according to claim 9, characterized in that: The preparation process of the tar suspension is as follows: the tar is first kept warm in an oven at 70° C. for 30 minutes, and then a silane coupling agent or ethyl silicate is added for stirring. After the stirring is completed, water is added after cooling to room temperature to obtain the tar suspension.